Healthcare staff perceptions towards influenza and potential COVID-19 vaccination in the 2020 pandemic context. (June 2021) - Robbins, T.; Berry, L.; Wells, F.; Randeva, H.; Laird, S.
Summary: The COVID-19 pandemic generated renewed focus on infectious disease transmission in healthcare settings. This study aimed to evaluate staff perceptions towards influenza vaccination in the COVID-19 context. All healthcare workers within a major UK tertiary referral hospital were invited to answer a survey conducted from September 2 nd to 13 th, 2020. In all, 593 responses were received across a spectrum of roles; 44% reported they were more likely to get an influenza vaccine this year due to COVID-19; however, 10% felt that an influenza vaccine was less important due to social distancing. Additional questions evaluated intention to receive COVID-19 vaccination. There were substantial differences of opinion between staff groups.